DETERMINASI PERILAKU KEUANGAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MERCU BUANA YOGYAKARTA - Linda Sari; Zaenal Wafa (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to determine and analyze the influence of financial accounting learning, financial literacy, and financial education in the family on the financial behavior of students of the Faculty of Economics, Mercu Buana University, Yogyakarta. The population in this study were all Accounting students of the Faculty of Economics, Mercu Buana University, Yogyakarta. The sample in this study was taken using a non-probability method, using a purposive sampling technique. The analysis technique used the SPSS analysis tool. The results of the study stated that based on the results of the regression analysis that had been carried out, partial hypothesis testing through the t test showed that the Financial Accounting Learning variable had a significance value of 0.321, which was greater than the significance level of 0.05. In addition, the calculated t value of 0.998 was smaller than the t table value of 1.990. Thus, the first hypothesis (H1) which stated that Financial Accounting Learning had a positive effect on Student Financial Behavior was not empirically proven, so H₀ was accepted and Hₐ was rejected. Based on the results of the second hypothesis testing through a partial t test, a significance value of 0.000 was obtained which was smaller than the significance level of 0.05. In addition, the calculated t value of 4.472 is greater than the t table value of 1.990. This result indicates that the second hypothesis (H2) which states that Financial Literacy has a positive effect on Student Financial Behavior is empirically proven, so that H₀ is rejected and Hₐ is accepted. Based on the results of testing the third hypothesis through a partial t test, a significance value of 0.001 is obtained, which is smaller than the significance level of 0.05. In addition, the calculated t value of 3.449 is greater than the t table of 1.990. This result indicates that the third hypothesis (H3), which states that Financial Education in the Family has a positive effect on Student Financial Behavior, is empirically proven, so that H₀ is rejected and Hₐ is accepted. Based on the results of testing the fourth hypothesis through a simultaneous F test, a significance value of 0.000 is obtained, which is smaller than the significance level of 0.05. In addition, the calculated F value of 32.447 is greater than the F table value of 2.72. These results indicate that the fourth hypothesis (H4), which states that Financial Accounting Learning, Financial Literacy, and Financial Education in the Family simultaneously have a positive influence on Student Financial Behavior, is empirically proven.